Preparation method of hollow copper oxide nano material

By using oxalic acid as the core for micro-reduction in the preparation of hollow copper oxide, an oxygen-deficient system was formed, and the existing hollow copper oxide process difficulties were solved through differentiated coating technology, and the effect of efficient preparation and improving photocatalytic performance was achieved.

CN119637925APending Publication Date: 2025-03-18ZHEJIANG YIMU TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411810268.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The difficulty of existing hollow copper oxide processes lies in the long reaction time, strict requirements on temperature and pH, and it is difficult to obtain a hollow structure.

Method used

Oxalic acid is used as the core to perform micro-reduction in the non-aqueous reaction system to form an oxygen-deficient system, increase the surfactivity of copper oxide, and achieve differentiated coating by dissolution differences between oxalic acid, ethyl cellulose and copper acetylacetonate.

Benefits of technology

The efficient preparation of hollow copper oxide nanomaterials is achieved, the copper oxide surfactivity is increased, and the photocatalytic performance of the material is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005180381290000071
    Figure BDA0005180381290000071
Patent Text Reader

Abstract

The invention belongs to the field of new materials, and particularly relates to a preparation method of a hollow copper oxide nano material, which comprises the following steps: adding oxalic acid into chloroform, uniformly stirring, then putting into a ball mill for reaction, and carrying out low-temperature ball milling treatment for 10-30 minutes to obtain oxalic acid fine powder liquid; adding copper acetylacetonate into the oxalic acid fine powder liquid, adding ethyl cellulose, stirring at low temperature, and filtering to obtain coated oxalic acid particles; putting the coated oxalic acid particles into a reaction kettle, carrying out static pressure reaction for 2-4 hours, and then carrying out light treatment for 10-20 minutes to obtain copper oxide-oxalic acid particles with porous surfaces; and putting the copper oxide-oxalic acid particles into a sealed reaction kettle, and carrying out vacuum constant-temperature reaction for 2-4 hours to obtain hollow copper oxide nano porous microspheres, namely the hollow copper oxide nano material. According to the invention, the process difficulty of the existing hollow copper oxide is solved, oxalic acid is used as an inner core to carry out a non-aqueous reaction system, and the copper oxide on the specific surface is subjected to micro-reduction by virtue of the reduction of oxalic acid to form an anoxic system of the specific surface, so that the surface activity of the copper oxide is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of new materials, and specifically relates to a method for preparing a hollow copper oxide nanomaterial. Background Art

[0002] With the development of human society, energy and environmental issues have become increasingly prominent and have attracted widespread attention, and modern environmental protection technologies have also developed rapidly. Gas-sensing and catalytic materials with excellent performance have important applications in the fields of air quality detection, safe production, and pollutant degradation.

[0003] As an important transition metal oxide, copper oxide is a typical p-type semiconductor material with a band gap of 1.2eV. Nano copper oxide has unusual properties in the fields of electricity, magnetism, catalysis, etc. due to its surface effect, quantum size effect, and Kubo effect. Therefore, the preparation, performance and application of nano copper oxide have attracted widespread attention in recent years. The crystal morphologies of copper oxide reported in the literature mainly include spheres, rods, ribbons, lines, three-dimensional hierarchical microstructures, including sea urchins, hollow spheres, etc. The main preparation methods of nano copper oxide are: room temperature solid phase reaction method, low temperature solid phase coordination chemical reaction method, controlled double jet liquid phase precipitation technology, sonochemical method, improved sol-gel method, alcohol thermal method, rapid liquid phase precipitation method, hydrothermal-solvothermal method, etc. However, these methods have a long reaction time, strict requirements on the temperature and pH of the reaction system, and it is not easy to obtain a hollow structure by the above methods. Summary of the invention

[0004] In view of the problems in the prior art, the present invention provides a method for solving the process difficulties of the existing hollow copper oxide, using oxalic acid as the core, carrying out a non-aqueous reaction system, and utilizing the reduction of oxalic acid to slightly reduce the copper oxide on the specific surface, forming an oxygen-deficient system on the specific surface, thereby greatly increasing the surface activity of the copper oxide.

[0005] In order to achieve the above technical objectives, the technical solution of the present invention is:

[0006] A method for preparing a hollow copper oxide nanomaterial comprises the following steps:

[0007] Step 1, adding oxalic acid to chloroform and stirring evenly, then putting it into a ball mill for reaction and low-temperature ball milling for 10-30 minutes to obtain oxalic acid fine powder liquid; the concentration of oxalic acid in chloroform in step 1 is 30-60g / L, the stirring speed is 1000-2000r / min, the temperature of the low-temperature ball mill is 2-10°C, and the ball milling pressure is 2-4MPa. Further, the low-temperature ball mill is a sealed ball mill to prevent the natural volatilization of chloroform, while refining and dispersing the oxalic acid;

[0008] Step 2, adding copper acetylacetonate to oxalic acid fine powder liquid, adding ethyl cellulose and stirring at low temperature, filtering to obtain coated oxalic acid particles; the concentration of the copper acetylacetonate in the oxalic acid fine powder liquid is 70-130g / L, the addition rate of the copper acetylacetonate is 1-2g / min, the addition amount of the ethyl cellulose is 0.1-0.7% of the mass of the copper acetylacetonate, the stirring rate of the low temperature stirring is 500-1000r / min, and the temperature is 0-5°C; further, the coated oxalic acid particles are subjected to a constant temperature extrusion treatment after filtration, the temperature is 60-80°C, and the pressure is 1-2MPa;

[0009] Step 3, placing the coated oxalic acid particles in a reactor, statically reacting for 2-4 hours, and then light-treating for 10-20 minutes to obtain surface porous copper oxide-oxalic acid particles, the temperature in the reactor is 100-120°C, the atmosphere in the reactor is: ozone 10-30%, water vapor 5-10%, nitrogen remaining, static pressure of 0.3-0.6MPa, temperature of 120-150°C; the ultraviolet light intensity of the light treatment is 5-10W / cm 2 , the temperature is 100-120℃;

[0010] Step 4, placing the copper oxide-oxalic acid particles in a sealed reactor and reacting them at a constant temperature in a vacuum for 2-4 hours to obtain hollow copper oxide nanoporous microspheres, i.e., hollow copper oxide nanomaterials; the temperature of the vacuum constant temperature reaction is 400-500°C.

[0011] The hollow copper oxide nanomaterial is used as a photocatalytic material.

[0012] It can be seen from the above description that the present invention has the following advantages:

[0013] 1. The present invention solves the technical difficulties of the existing hollow copper oxide, uses oxalic acid as the core, conducts a non-aqueous reaction system, and utilizes the reduction of oxalic acid to slightly reduce the copper oxide on the specific surface, forming an oxygen-deficient system on the specific surface, thereby greatly increasing the surface activity of the copper oxide.

[0014] 2. The present invention utilizes the solubility difference of oxalic acid, ethyl cellulose and copper acetylacetonate to realize differentiated coating and achieve the effect of surface coating. At the same time, the stability of oxalic acid itself is utilized to achieve the stability of the core structure.

[0015] 3. The present invention uses oxalic acid as the core structure, realizes stable storage in a temperature-controlled manner, and decomposes at an elevated temperature to form a reduction system to slightly reduce the surface copper oxide, thereby creating an oxygen-deficient system for the surface copper oxide. DETAILED DESCRIPTION

[0016] The present invention is described in detail with reference to the embodiments, but no limitation is imposed on the claims of the present invention.

[0017] Example 1

[0018] A method for preparing a hollow copper oxide nanomaterial comprises the following steps:

[0019] Step 1, adding oxalic acid to chloroform and stirring evenly, then putting it into a ball mill for reaction and low-temperature ball milling for 10 minutes to obtain oxalic acid fine powder liquid; the concentration of oxalic acid in chloroform in the step 1 is 30g / L, the stirring speed is 1000r / min, the temperature of the low-temperature ball mill is 2°C, the ball milling pressure is 2MPa, and the low-temperature ball mill is a sealed ball mill to prevent the natural volatilization of chloroform, and at the same time, the oxalic acid is refined and dispersed; the oxalic acid adopts nano-oxalic acid, and the steps of nano-oxalic acid include: a, dissolving oxalic acid in ethanol and stirring evenly, the stirring speed is 100r / min, the concentration of oxalic acid in ethanol is 30g / L, then flushing in anhydrous ether and stirring evenly to obtain an oxalic acid mixed solution, the amount of anhydrous ether added is twice the volume of ethanol, and the stirring speed is 1000r / min; b, spraying the oxalic acid mixed solution into a xylene solution at a constant temperature and continuously stirring until it is completely suspended and dispersed to obtain a suspension, and the spraying area of ​​the oxalic acid mixed solution at a constant temperature spraying is 100cm 2 , the spray volume is 0.1mL / min, the spray port temperature is 50°C, the temperature of the xylene is 100°C, and the continuous stirring speed is 500r / min, and the gas after the spray is respectively recovered from ethanol and anhydrous ether by the temperature difference method; c, the suspension is converted into a precipitate, and the nano-oxalic acid is obtained by drying. The method for converting the suspension into a precipitate adopts a spray method, and the spray method is to spray the suspension into a sealed reactor at a constant temperature, seal and stand for 2-3h, and then release the pressure to obtain nano-oxalic acid, the temperature of the constant temperature spray is 13-140°C, the temperature of the constant temperature standing is 140-150°C, and the pressure is 0.2-0.3MPa; here, the suspension is sprayed into a sealed reactor at a constant temperature, and the pressure is released after the seal is stood for 2h to obtain nano-oxalic acid, the temperature of the constant temperature spray is 130°C, the temperature of the constant temperature standing is 140°C, and the pressure is 0.2MPa;

[0020] Step 2, adding copper acetylacetonate to oxalic acid fine powder liquid, adding ethyl cellulose and stirring at low temperature, filtering to obtain coated oxalic acid particles; the concentration of the copper acetylacetonate in the oxalic acid fine powder liquid is 70g / L, the addition rate of the copper acetylacetonate is 1g / min, the addition amount of the ethyl cellulose is 0.1% of the mass of the copper acetylacetonate, the stirring rate of the low temperature stirring is 500r / min, and the temperature is 0°C; further, the coated oxalic acid particles are subjected to a constant temperature extrusion treatment after filtration, the temperature is 60°C, and the pressure is 1MPa;

[0021] Step 3, placing the coated oxalic acid particles in a reactor, statically reacting for 2 hours, and then irradiating with light for 10 minutes to obtain surface porous copper oxide-oxalic acid particles, the temperature in the reactor is 100°C, the atmosphere in the reactor is: 10% ozone, 5% water vapor, and the rest nitrogen, the static pressure is 0.3MPa, and the temperature is 120°C; the ultraviolet light intensity of the light treatment is 5W / cm 2 , temperature is 100℃;

[0022] Step 4, placing the copper oxide-oxalic acid particles in a sealed reactor and reacting them at a constant temperature in a vacuum for 2 hours to obtain hollow copper oxide nanoporous microspheres, i.e., hollow copper oxide nanomaterials; the temperature of the vacuum constant temperature reaction is 400°C.

[0023] The copper oxide nanomaterial prepared in this embodiment has a particle size of about 800 nm and a product purity of 99.8%.

[0024] Example 2

[0025] A method for preparing a hollow copper oxide nanomaterial comprises the following steps:

[0026] Step 1, adding oxalic acid to chloroform and stirring evenly, then putting it into a ball mill for reaction and low-temperature ball milling for 30 minutes to obtain oxalic acid fine powder liquid; the concentration of oxalic acid in chloroform in step 1 is 60g / L, the stirring speed is 2000r / min, the temperature of the low-temperature ball mill is 10°C, the ball milling pressure is 4MPa, and the low-temperature ball mill is a sealed ball mill to prevent the natural volatilization of chloroform, while refining and dispersing the oxalic acid; the oxalic acid adopts nano-oxalic acid, based on the extremely small particle size of the nano-oxalic acid and the formation of uniform dispersion in chloroform, so as to increase the specific surface area and achieve the effect of refining the hollow copper oxide structure; the step of nano-oxalic acid comprises: a, dissolving oxalic acid in ethanol Stir evenly at a stirring speed of 200 r / min. The concentration of oxalic acid in ethanol is 90 g / L. Then, anhydrous ether is added and stirred evenly to obtain an oxalic acid mixed solution. The amount of anhydrous ether added is 10 times the volume of ethanol. The stirring speed is 2000 r / min. Ethanol has good solubility for oxalic acid. First, the oxalic acid is completely dissolved and evenly dispersed in the entire ethanol. Then, the volume of ethanol is expanded to several times the original volume by using the mutual solubility system of anhydrous ether and ethanol to achieve good oxalic acid dispersibility. b. Constant temperature spraying the oxalic acid mixed solution into the xylene solution and continuously stirring until it is completely suspended and dispersed to obtain a suspension. The spray area of ​​the constant temperature spraying of the oxalic acid mixed solution is 200 cm 2, the spray volume is 0.3mL / min, the temperature of the spray port is 60°C, the temperature of the xylene is 110°C, and the continuous stirring speed is 500-1000r / min. The gas after the spray adopts a temperature difference method to recover ethanol and anhydrous ether respectively. In this step, during the constant temperature spraying of oxalic acid, the anhydrous ether is converted into a gaseous state under the temperature condition of the spray port, and the ethanol is expanded and dispersed, and the spray dispersion of the spray port is coordinated to achieve a further dispersion effect. As the ethanol is atomized and falls into the xylene, the temperature of the xylene causes the ethanol to be converted into steam and discharged directly, and the oxalic acid as a solute is directly dispersed and settled in the xylene as a precipitate, thereby uniformly Uniform dispersion; c, converting the suspension into a precipitate, drying to obtain nano-oxalic acid, the method for converting the suspension into a precipitate adopts a solvent washing method, the solvent washing method is to filter the suspension, then add it to chloroform and stir it evenly, filter and dry it to obtain nano-oxalic acid, the concentration of the precipitate in chloroform is 5-10g / L, the stirring speed is 500-1000r / min, and the drying temperature is 70-80°C; here, the suspension is filtered, then added to chloroform and stirred evenly, filtered and dried to obtain nano-oxalic acid, the concentration of the precipitate in chloroform is 5g / L, the stirring speed is 500r / min, and the drying temperature is 70°C;

[0027] Step 2, adding copper acetylacetonate to oxalic acid fine powder liquid, adding ethyl cellulose and stirring at low temperature, filtering to obtain coated oxalic acid particles; the concentration of the copper acetylacetonate in the oxalic acid fine powder liquid is 130g / L, the addition rate of the copper acetylacetonate is 2g / min, the addition amount of the ethyl cellulose is 0.7% of the mass of the copper acetylacetonate, the stirring rate of the low temperature stirring is 1000r / min, and the temperature is 5°C; the coated oxalic acid particles are subjected to a constant temperature extrusion treatment after filtration, the temperature is 80°C, and the pressure is 2MPa;

[0028] Step 3, placing the coated oxalic acid particles in a reactor, statically reacting for 4 hours, and then irradiating with light for 20 minutes to obtain surface porous copper oxide-oxalic acid particles, the temperature in the reactor is 120°C, the atmosphere in the reactor is: 30% ozone, 10% water vapor, and the rest nitrogen, the static pressure is 0.6MPa, and the temperature is 150°C; the ultraviolet light intensity of the light treatment is 10W / cm 2 , the temperature is 120℃;

[0029] Step 4, placing the copper oxide-oxalic acid particles in a sealed reactor and reacting them at a constant temperature in a vacuum for 4 hours to obtain hollow copper oxide nanoporous microspheres, i.e., hollow copper oxide nanomaterials; the temperature of the vacuum constant temperature reaction is 500°C.

[0030] The copper oxide nanomaterial prepared in this embodiment has a particle size of about 200 nm and a product purity of 99.9%.

[0031] Example 3

[0032] A method for preparing a hollow copper oxide nanomaterial comprises the following steps:

[0033] Step 1, adding oxalic acid to chloroform and stirring evenly, then putting it into a ball mill for reaction and low-temperature ball milling for 20 minutes to obtain oxalic acid fine powder liquid; the concentration of oxalic acid in chloroform in step 1 is 50g / L, the stirring speed is 1500r / min, the temperature of the low-temperature ball mill is 8°C, the ball milling pressure is 3MPa, and the low-temperature ball mill is a sealed ball mill to prevent the natural volatilization of chloroform, while refining and dispersing the oxalic acid; the oxalic acid adopts nano-oxalic acid, based on the extremely small particle size of the nano-oxalic acid and the formation of uniform dispersion in chloroform, the specific surface is increased and the hollow copper oxide structure is refined; the steps of the nano-oxalic acid include: a, dissolving oxalic acid in ethanol Stir evenly at a stirring speed of 150 r / min. The concentration of oxalic acid in ethanol is 70 g / L. Then, anhydrous ether is added and stirred evenly to obtain an oxalic acid mixed solution. The amount of anhydrous ether added is 8 times the volume of ethanol. The stirring speed is 1500 r / min. Ethanol has good solubility for oxalic acid. First, the oxalic acid is completely dissolved and evenly dispersed in the entire ethanol. Then, the volume of ethanol is expanded to several times the original volume by using the mutual solubility system of anhydrous ether and ethanol to achieve good oxalic acid dispersibility. b. The oxalic acid mixed solution is sprayed into the xylene solution at a constant temperature and continuously stirred until it is completely suspended and dispersed to obtain a suspension. The spray area of ​​the oxalic acid mixed solution sprayed at a constant temperature is 150 cm 2 The spray volume is 0.2 mL / min, the temperature of the spray port is 55°C, the temperature of the xylene is 105°C, and the continuous stirring speed is 900 r / min. The gas after the spray is respectively recovered from ethanol and anhydrous ether by a temperature difference method. In this step, during the constant temperature spraying of oxalic acid, anhydrous ether is converted into a gaseous state under the temperature condition of the spray port, and ethanol is expanded and dispersed, and the spray dispersion of the spray port is coordinated to achieve a further dispersion effect. As the ethanol is atomized and falls into the xylene, the temperature of the xylene causes the ethanol to be converted into steam and directly discharged, while the oxalic acid as a solute is directly dispersed and settled in the xylene as a precipitate. c. Convert the suspension into a precipitate, dry it to obtain nano-oxalic acid, wherein the method for converting the suspension into a precipitate adopts a spraying method, wherein the spraying method is to spray the suspension into a sealed reactor at a constant temperature, seal it and let it stand for 2-3 hours, then release the pressure to obtain nano-oxalic acid, the temperature of the constant temperature spray is 130-140°C, the temperature of the constant temperature standing is 140-150°C, and the pressure is 0.2-0.3MPa; herein, the suspension is sprayed into a sealed reactor at a constant temperature, sealed and let it stand for 3 hours, then release the pressure to obtain nano-oxalic acid, the temperature of the constant temperature spray is 140°C, the temperature of the constant temperature standing is 150°C, and the pressure is 0.3MPa;

[0034] Step 2, adding copper acetylacetonate to oxalic acid fine powder liquid, adding ethyl cellulose and stirring at low temperature, filtering to obtain coated oxalic acid particles; the concentration of the copper acetylacetonate in the oxalic acid fine powder liquid is 70-130g / L, the addition rate of the copper acetylacetonate is 2g / min, the addition amount of the ethyl cellulose is 0.5% of the mass of the copper acetylacetonate, the stirring rate of the low temperature stirring is 500-1000r / min, and the temperature is 5°C; further, the coated oxalic acid particles are subjected to a constant temperature extrusion treatment after filtration, the temperature is 70°C, and the pressure is 2MPa;

[0035] Step 3, placing the coated oxalic acid particles in a reactor, statically reacting for 3 hours, and then irradiating with light for 15 minutes to obtain surface porous copper oxide-oxalic acid particles, the temperature in the reactor is 110°C, the atmosphere in the reactor is: 20% ozone, 8% water vapor, and the rest nitrogen, the static pressure is 0.5MPa, and the temperature is 140°C; the ultraviolet light intensity of the light treatment is 8W / cm 2 , the temperature is 110℃;

[0036] Step 4, placing the copper oxide-oxalic acid particles in a sealed reactor and reacting them at a constant temperature in a vacuum for 3 hours to obtain hollow copper oxide nanoporous microspheres, i.e., hollow copper oxide nanomaterials; the temperature of the vacuum constant temperature reaction is 450°C.

[0037] The copper oxide nanomaterial prepared in this embodiment has a particle size of about 500 nm and a product purity of 99.8%.

[0038] Performance Testing

[0039] The products of the above-mentioned Examples 1-3 and commercially available nano copper oxide (500nm) were used as experimental products and comparative examples to degrade 70mg / L of methyl orange solution. The light source used in the photocatalytic experiment was a 300W xenon lamp. Before irradiation, the methyl orange solution containing the catalytic material was stirred in the dark for 30 minutes and then irradiated after reaching adsorption equilibrium. The concentration of methyl orange dye was measured by a spectrophotometer and the degradation rate was calculated. In the experiment of photocatalytic evaluation of catalytic activity, the degradation evaluation was as follows:

[0040]

[0041] In summary, the present invention has the following advantages:

[0042] 1. The present invention solves the technical difficulties of the existing hollow copper oxide, uses oxalic acid as the core, conducts a non-aqueous reaction system, and utilizes the reduction of oxalic acid to slightly reduce the copper oxide on the specific surface, forming an oxygen-deficient system on the specific surface, thereby greatly increasing the surface activity of the copper oxide.

[0043] 2. The present invention utilizes the solubility difference of oxalic acid, ethyl cellulose and copper acetylacetonate to realize differentiated coating and achieve the effect of surface coating. At the same time, the stability of oxalic acid itself is utilized to achieve the stability of the core structure.

[0044] 3. The present invention uses oxalic acid as the core structure, realizes stable storage in a temperature-controlled manner, and decomposes at an elevated temperature to form a reduction system to slightly reduce the surface copper oxide, thereby creating an oxygen-deficient system for the surface copper oxide.

[0045] It is understood that the above specific description of the present invention is only used to illustrate the present invention and is not limited to the technical solutions described in the embodiments of the present invention. Those skilled in the art should understand that the present invention can still be modified or replaced by equivalents to achieve the same technical effects; as long as the use requirements are met, they are within the protection scope of the present invention.

Claims

1. A method for preparing a hollow copper oxide nanomaterial, characterized in that: The steps include: Step 1, adding oxalic acid to chloroform and stirring evenly, then putting it into a ball mill for reaction and low temperature ball milling for 10-30 minutes to obtain oxalic acid fine powder liquid; Step 2, adding copper acetylacetonate to oxalic acid fine powder solution, adding ethyl cellulose and stirring at low temperature, and filtering to obtain coated oxalic acid particles; Step 3, placing the coated oxalic acid particles into a reactor, reacting under static pressure for 2-4 hours, and then treating with light for 10-20 minutes to obtain copper oxide-oxalic acid particles with porous surfaces; Step 4, placing the copper oxide-oxalic acid particles in a sealed reactor and reacting at a constant temperature in a vacuum for 2-4 hours to obtain hollow copper oxide nanoporous microspheres, i.e., hollow copper oxide nanomaterials.

2. The method for preparing the hollow copper oxide nanomaterial according to claim 1, characterized in that: The concentration of oxalic acid in chloroform in step 1 is 30-60 g / L, the stirring speed is 1000-2000 r / min, the temperature of the low-temperature ball mill is 2-10° C., and the ball milling pressure is 2-4 MP.

3. The method for preparing the hollow copper oxide nanomaterial according to claim 1, characterized in that: The low temperature ball milling in step 1 is a sealed ball milling.

4. The method for preparing the hollow copper oxide nanomaterial according to claim 1, characterized in that: The concentration of copper acetylacetonate in the oxalic acid fine powder solution in step 2 is 70-130 g / L, the addition rate of copper acetylacetonate is 1-2 g / min, the addition amount of ethyl cellulose is 0.1-0.7% of the mass of copper acetylacetonate, the stirring speed of low-temperature stirring is 500-1000 r / min, and the temperature is 0-5°C.

5. The method for preparing the hollow copper oxide nanomaterial according to claim 1, characterized in that: The coated oxalic acid particles in step 2 are subjected to a constant temperature extrusion treatment after filtration, with a temperature of 60-80° C. and a pressure of 1-2 MPa.

6. The method for preparing the hollow copper oxide nanomaterial according to claim 1, characterized in that: The temperature in the reactor in step 3 is 100-120°C, the atmosphere in the reactor is: 10-30% ozone, 5-10% water vapor, and the remainder nitrogen, the static pressure is 0.3-0.6MPa, and the temperature is 120-150°C.

7. The method for preparing the hollow copper oxide nanomaterial according to claim 1, characterized in that: The ultraviolet light intensity of the light treatment in step 3 is 5-10W / cm 2 , the temperature is 100-120℃.

8. The method for preparing the hollow copper oxide nanomaterial according to claim 1, characterized in that: The temperature of the vacuum constant temperature reaction in step 4 is 400-500°C.

9. The method for preparing the hollow copper oxide nanomaterial according to claim 1, characterized in that: The hollow copper oxide nanomaterial is used as a photocatalytic material.